The Nexus of Foreign Direct Investment and Economic Growth from the Open Economy Perspective - Sagasukom, Suhsmitha; Sanusi, Nur Azura (International Journal of Economics and Financial Issues, 2025)
The purpose of this research is to study the impact of Foreign Direct Investment (FDI) on Malaysian GDP growth under the analysis based on a time series model for the period 1974-2023. The purpose of this research is to study how FDI, exports, and inflation will respond to each other in creating Malaysian economic growth based on ARDL and ARIMA models. The study uses secondary data from sources like the World Bank. It tests the variables for stationarity and models short-run and long-run dynamics using ARDL. The ARIMA model is applied to forecast GDP trends. The background includes Malaysia’s economic transformation from a rural-based to an export-oriented industrial base. The literature review confirms prior empirical evidence supporting FDI’s contribution to capital accumulation, technology transfer, and productivity, moderated by institutional quality and inflation. The ARDL results reveal a statistically significant long-run relationship between FDI and GDP growth, while exports and inflation exert opposite impacts. Based on the ARIMA model, there is an expected positive and consistent pattern of GDP growth through 2030, in support of the long-term FDI benefit to economic performance. This report stresses the importance of judicious macroeconomic policies, human capital formation, trade openness, regulatory reform, and infrastructure building in sustaining FDI inflows as well as the future growth of Malaysia.